Academic Senate Minutes 2004-03-04 - Academic Senate:::::::::
Presentation on Green Music Center in Warren Auditorium. Agenda approved. Minutes of 2/5/04 approved. Early Childhood Education Certificate approved. Special Guests: Faculty Trustee Kathy Kaiser and Statewide Senate Chair Bob Cherny. Joint Doctoral Program in Education – Second Reading - approved. Provost Ochoa report